Origins of Alien Species and Plant Invasion in India as Tapped from Kurma Purana - Patil, D A (Plantae Scientia, 2021)
Ancient Sanskrit Puranas are literary heritage of India. They are studied from different perspectives but appeared largely neglected from the viewpoint of plant invasion in Indian territory. The present attempt dealt with the alien plant species as encoded in Sanskrit plant names in various verses of Kurma Purana. As many as 24 alien plant species belong to 23 genera of 16 families of angiosperms. They are analysed carefully floristically, habital categories and status regarding cultivation or naturalization. They are also studied for their nativity consulting relevant taxonomic literature. The data indirectly also indicated about utilities and awareness about classification of plants based on habits. Such investigations are warranted for better understanding of the development of natural wealth in past.